Management of stem rot of rice with resistance inducing chemicals and fungicides - and B.L. JALALI*, A. KUMAR, RAM SINGH (Indian Phytopathology, 2003)
The efficacy of resistance inducing chemicals and fungicides against stem rot of rice was evaluated in a field experiment. Of the six resistance inducing chemicals, benzoic acid was found better over other chemicals in reducing the stem rot incidence and severity followed by naphthalene acetic acid. Amongst nine fungicides, propiconazole was found most promising and provided 47.5 per cent and 26.5 per cent reduction in disease incidence and severity, respectively along with 7.7 per cent increase in grain yield followed by isoprothiolane. Three sprays of propiconazole at disease initiation, boot and flowering stages provided maximum disease control along with significant increase in grain yield followed by two sprays at disease initiation and boot stages. The effective fungicides provided better disease control as compared to resistance inducing chemicals.